Transferability of European-derived Alzheimer's disease polygenic risk scores across multiancestry populations - Nicolas, Aude; Sherva, Richard; Grenier-Boley, Benjamin; Kim, Yoontae; Kikuchi, Masataka; Timsina, Jigyasha; de Rojas, Itziar; Dalmasso, María Carolina; Zhou, Xiaopu; Le Guen, Yann; Arboleda-Bustos, Carlos E; Camargos Bicalho, Maria Aparecida; et al. (Nature genetics, 2025)
A polygenic score (PGS) for Alzheimer's disease (AD) was derived recently from data on genome-wide significant loci in European ancestry populations. We applied this PGS to populations in 17 European countries and observed a consistent association with the AD risk, age at onset and cerebrospinal fluid levels of AD biomarkers, independently of apolipoprotein E locus (APOE). This PGS was also associated with the AD risk in many other populations of diverse ancestries. A cross-ancestry polygenic risk score improved the association with the AD risk in most of the multiancestry populations tested when the APOE region was included. Finally, we found that the PGS/polygenic risk score captured AD-specific information because the association weakened as the diagnosis was broadened. In conclusion, a simple PGS captures the AD-specific genetic information that is common to populations of different ancestries, although studies of more diverse populations are still needed to better characterize the genetics of AD.
Keywords: celogenomová asociační studie; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Humans; běloši; genetické rizikové skóre; Evropa; jednonukleotidový polymorfismus; Female; rizikové faktory; Aged; White People; senioři; lidé; Alzheimer Disease; Biomarkers; Europe; Alzheimerova nemoc; ženské pohlaví; biologické markery; Male; Genetic Predisposition to Disease; genetická predispozice k nemoci; Genetic Risk Score; Apolipoproteins E; Genome-Wide Association Study; multifaktoriální dědičnost; mužské pohlaví; apolipoproteiny E; Risk Factors